INCREASING COMMUNITY EMPOWERMENT IN FACING COVID-19 THROUGH HUMANITARIAN ACTIVITIES; HEALTHY KITCHEN - ., Desmawati; Agustina, Agustina; Samaria, Dora; Ritanti, Ritanti; Ayu Marcelina, Lina; Sholihatunnisa, Dini; Dewi Sulistyawati, Pricilia; Valeryta Dewi, Geofunny; Azzahra, Fatimah; Alif Fatwa Supendi, Kiana (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Covid-19 has not been reported to be zero, and the cases are still going up and down. This indicates that people are always vigilant in dealing with Covid-19. Therefore, community empowerment in preventing and adapting to Covid-19 in Pamulang Timur Banten is needed, which is one of the buffer areas for the capital Jakarta as the epicenter of Covid-19. Community service aims to provide motivation, guidance, and assistance, and increase community participation in the COVID-19 healthy kitchen as one of the humanitarian projects to deal with COVID-19. The methods used are counseling, group discussion forums, interviews, observations, the establishment of a covid-19 kitchen, training, and assistance in managing healthy food. The results of this program are the motivation of the PKK, health cadres, and the Covid-19 task force team to carry out humanitarian projects COVID-19 and the realization of a COVID-19 healthy kitchen. The covid-19 kitchen is oriented starting by motivating residents to share by hanging basic food materials on the hanging food boards provided, then cooking them, and delivering them to residents who are exposed to COVID-19 (who are self-isolating at home).